2015
DOI: 10.1017/ice.2015.204
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control Implications of Protracted Lengths of Stay With Noninfluenza Viral Influenza-Like Illnesses in Hospitalized Adults During the 2015 Influenza A (H3N2) Epidemic

Abstract: We agree that the use of rapid ATP testing has a growing body of published support. However, the lack of common acceptance for rapid ATP testing at this point in time is well expressed in the EPIC 3 Guidelines (2014) from an expert committee in the United Kingdom. 2 Unfortunately, Ms Roady somewhat misses the point of our paper. In our study, we did not attempt to equate rapid ATP testing with detection of bacterial contamination. We showed that the variability that occurs when measuring responses to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although we can begin to predict patterns of respiratory virus circulation as surveillance and detection capacities improve (9), viruses may be identified outside their normal seasonal infection patterns due to patient activities, such as travel to regions where the virus is currently circulating (10). Knowing the travel history combined with active pathogen surveillance (e.g., identifying a patient who presents during a North American summer with acute respiratory infection after travel to the Southern Hemisphere where FLU or RSV is circulating) can help direct appropriate infection prevention and control measures, as not all respiratory viruses require the same level of patient isolation (11,12).…”
Section: Epidemiology and Clinical Presentation Of Acute Respiratory mentioning
confidence: 99%
“…Although we can begin to predict patterns of respiratory virus circulation as surveillance and detection capacities improve (9), viruses may be identified outside their normal seasonal infection patterns due to patient activities, such as travel to regions where the virus is currently circulating (10). Knowing the travel history combined with active pathogen surveillance (e.g., identifying a patient who presents during a North American summer with acute respiratory infection after travel to the Southern Hemisphere where FLU or RSV is circulating) can help direct appropriate infection prevention and control measures, as not all respiratory viruses require the same level of patient isolation (11,12).…”
Section: Epidemiology and Clinical Presentation Of Acute Respiratory mentioning
confidence: 99%
“…Two studies report that the results of MRVP affected infection control management, but also mention that logistical problems can limit their effect [ 35 , 37 ]. Braybrook et al found that infection control measures of hospitalized children were affected by MRVP in one-quarter of cases, but the value of testing was directly related to the number of isolation rooms available.…”
Section: Discussionmentioning
confidence: 99%